Fault Tree Analysis of Waste Quantity Indicator Failure on Boeing 737 NG - Rommy Rayhan Muhammad; Sri Mulyani; Fajar Khanif Rahmawati; Bangga Dirgantara Adiputra; Elisabeth Anna Prattiwi; Agung Prakoso (Vortex, 2026)
The waste quantity indicator on the Boeing 737 NG attendant panel plays a vital role in providing information regarding the waste tank volume during flight. In practice, however, data discrepancies frequently occur. This condition can trigger unnecessary technical reports, disrupt operational efficiency, and increase aircraft maintenance costs. The results of the study indicate that there are four main failure pathways: damage to the point level sensor, continuous level sensor, logic control module (LCM), and the connection on the Attendant Control Panel (ACP). Out of the 16 analyzed defect data, 43.75% were caused by point level sensor failures. The breakdown of the FTA structure generated eight Minimum Cut Sets (MCS) as triggers for the Top Event. These findings serve as a basis for developing inspection strategies and preventive maintenance to enhance the reliability of the aircraft waste indicator system